Automatic control of motors through Simocode pro, and its effect on the performance of the process of filling and dispensing of chemical inputs - Omar Chamorro-Atalaya; Augusto Sanchez-Ayte; Carlos Dávila-Ignacio; Orlando Ortega-Galicio; Nestor Alvarado-Bravo; Almintor Torres-Quiroz; Florcita Aldana-Trejo (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This article aims to describe the design of an automatic control system for the automated management of motor drives through Simocode pro; and determine the effect from the quantitative point of view on the performance of the filling and dispatch process of chemical inputs from the perspective of dispatch time and the amount of input spilled in the tank filling stage. For this, the programming of the programmable logic controller was carried out using the simatic step 7 software, then the distributed control system (DCS Siemens S410) was programmed, using the PCS7 V8.1 software, where the control logic and simocode pro integration is carried out through the profibus protocol, which is monitored from an human-machine interface (HMI) interface. Once the control system was implemented, it was possible to reduce the operating time from 60 minutes on average to 35 minutes, which reflects an improvement of 41.66%; this in turn generates an increase in the number of tank filling by 62.84%. Likewise, it is possible to reduce the amount of chemical inputs spilled in the filling stage; this improvement represents 88.60%.